A diagenetic control on the Early Triassic Smithian–Spathian carbon isotopic excursions recorded in the marine settings of the Thaynes Group (Utah, USA). Issue 3 (4th February 2016) - Thomazo, C.; Vennin, E.; Brayard, A.; Bour, I.; Mathieu, O.; Elmeknassi, S.; Olivier, N.; Escarguel, G.; Bylund, K. G.; Jenks, J.; Stephen, D. A.; Fara, E.
Abstract: In the aftermath of the end‐Permian mass extinction, Early Triassic sediments record some of the largest Phanerozoic carbon isotopic excursions. Among them, a global Smithian‐negative carbonate carbon isotope excursion has been identified, followed by an abrupt increase across the Smithian–Spathian boundary (SSB; 250.8 Myr ago). This chemostratigraphic evolution is associated with palaeontological evidence that indicate a major collapse of terrestrial and marine ecosystems during the Late Smithian. It is commonly assumed that Smithian and Spathian isotopic variations are intimately linked to major perturbations in the exogenic carbon reservoir. We present paired carbon isotopes measurements from the Thaynes Group (Utah, USA) to evaluate the extent to which the Early Triassic isotopic perturbations reflect changes in the exogenic carbon cycle. The δ 13 Ccarb variations obtained here reproduce the known Smithian δ 13 Ccarb ‐negative excursion. However, the δ 13 C signal of the bulk organic matter is invariant across the SSB and variations in the δ 34 S signal of sedimentary sulphides are interpreted here to reflect the intensity of sediment remobilization. We argue that Middle to Late Smithian δ 13 Ccarb signal in the shallow marine environments of the Thaynes Group does not reflect secular evolution of the exogenic carbon cycle but rather physicochemical conditions at the sediment–water interface leading to authigenic carbonate formation during early diagenetic processes.